NEW INFORMATION ON CRANIAL AND DENTAL FEATURES OF THE TRIASSIC ARCHOSAURIFORM REPTILE EUPARKERIA CAPENSIS - Senter Ph. (My University, 2003)
The course of the nasolacrimal duct, interdental plate morphology, and most details of tooth and denticle morphology have not previously been described in non-archosauriform reptilkes. Here I describe these details in the Triassic archosauriform Euparkeria capensis. The nasolacrimal canal opens orbitally via a pair of foramina between the lacrimal and prefrontal. The canal arches over the antorbital fenestra, as in archosaurs. The term 'interdental unit' is introduced for the unit composed of an interdental septum and its accompanying interdental plate. There is no demarcation between interdental plate and septum in E. capensis. The interdental units are heavily pitted on exposed surfaces. Like teeth, they are implanted in the dental groove and are separate from the surrounding bone and from each other. They are well positioned to serve as spacers between teeth, and to resist sagittal forces on teeth during prey capture. The teeth of E. capensis are labiolingually compressed, except for the nearly conical premaxillary teeth and mesialmost dentary tooth. Lateral teeth are serrated on mesial and distal keels. The denticles are low, rounded, and separated by grooves, and are slightly larger on the distal keel. Tooth morphology suggests carnivorous habits for Euparkeria.
Keywords: ARCHOSAURIFORMES; ARCHOSAUROMORPHA; EUPARKERIA; DENTITION; INTERDENTAL UNITS; NASOLACRIMAL CANAL; REPTILIA; Triassic; Mesozoic::Triassic; Мезозой::Триасовая